THERMO-MECHANICAL MODEL FOR CONCRETE PAVEMENT - Jakub Veselý; Vít Šmilauer (Acta Polytechnica CTU Proceedings)
This paper describes a numerical thermo-mechanical model for concrete pavement, implemented in OOFEM software. The thermal part is a heat transfer problem with appropriate initial and boundary conditions (sun irradiation, radiation and convection), calibrated from experimental data. Heat release from cement hydration is also included, calibrated for commonly used cements to demonstrate the difference that can be achieved with the binder selection. The mechanical part of the problem is composed of a 3D elastic concrete slab, subsoil Winkler-Pasternak elements and 1D interface elements, allowing separation in tension. The Winkler-Pasternak constants C1 and C2 were firstly determined from TP170 document and refined later from static load tests on the highway. The model validates well temperature field, static load test and provide several useful insight such as feasible time for summer casting, stress/strain fields and slab separation from the base.